Composição e distribuição da ictiofauna de tributários do Rio Mogi Guaçu e do Rio Corumbataí, Estado de São Paulo - Oliveira, Alexandre Kannebley de (Universidade Federal de São Carlos, 2006)
The composition and distribution of fish fauna from streams and creeks of Mogi Guaçu and Corumbataí river basins, at São Paulo State, were studied and compared. A watershed in the boundary of the geomorphological provinces Cuestas Basálticas and Depressão Periférica isolates the drainage systems of Mogi Guaçu and Tietê rivers, from which Corumbataí belongs. The works were focused in collection and identification of fish species from the streams Cabaceiras, Araras, Quilombo and Pântano (tributaries of the Mogi Guaçu River) and from creeks affluent of Corumbataí River, aiming to the realization of an inventory of the ichthyofauna in the region and to verify the similarity and distribution of species, associating them to geological and geographic events that occurred in these river drainages. The species lists of the two drainage systems were compared and particularities of each one were identified. The distribution of these species restricted to one or other drainage is analysed relative to relief. The drainages isolation is considered important factor acting in the occurrence of fish composition particularities in these small rivers. For inventory of species fish were collected in sites distributed in both mountainsides. A total of 16455 fish specimens belonging to 92 species were collected. Other fish species that occur in the study area were added to this preliminary list by the examination of lots deposited in LISDEBE (Laboratório de Ictiologia Sistemática da UFSCar) and from the studies in the Corumbataí River, summing 104 fish species. Eighty-one of these species were registered in affluent of the Mogi Guaçu River basin and 88 in the Corumbataí River. The 104 species are distributed in six orders: Characiformes (52 species), Siluriformes (40 species), Gymnotiformes (3 species), Cyprinodontiformes (2 species), Perciformes (6 species) and Synbranchiformes (1 species). Twenty-one species were restricted to one or another drainage, being 16 of these restricted to the Corumbataí, and five to the tributaries of Mogi Guaçu River. Some of the species that showed restriction in our study area to the Corumbataí River, or in the Tietê basin, are also encountered in the Paranapanema River, as Bryconamericus sp., Astyanax sp., Schizodon intermedius and Loricaria prolixa, and in the Paranaíba River, as Bryconamericus turiuba. Others are restricted to the Tietê River, as Corumbataia cuestae, Corydoras flaveolus, Planaltina glandipedis, Cyphocharax vanderi, Hypoptopomatinae gen. sp., Harttia sp. and Trichomycterus sp. About the species that showed to be restricted to the tributaries of Mogi Guaçu River basin (in our study area), Bunocephalus sp. only occurs in this basin and Corydoras difluviatilis also occurs in the headwaters of the rivers: Grande, São Francisco and Paranaíba, evidencing a shared biogeographical history among these drainages. The recognition of the upper Paraná River basin as a great area of endemism may be reevaluated not only on the strength of the results obtained, which indicate species of restrict distribution to one or another basin of affluent of the upper Paraná River, but chiefly in function of several work actually being developed, which have been demonstrated the existence of smaller areas in this great basin that presents species of restricted distribution. The lower stretches of Corumbataí River and tributaries of Mogi Guaçu River show several common species, including species of small body size and medium to great body size, widely distributed in the upper Paraná River basin, such as Acestrorhynchus lacustris, Piabina argentea, Salminus hilarii, those of the subfamily Cheirodontinae, the species of genus Leporinus, Schizodon nasutus, Prochilodus lineatus, Pimelodus maculatus, the species of genus Hypostomus, among others. Of the inventoried species, Astyanax sp., Bryconamericus sp., Odontostilbe sp., Bunocephalus sp., Hypoptopomatinae gen. sp., Harttia sp., Trichomycterus sp. e Laetacara sp. are probably new to science.
Keywords: Ictiologia; Peixe de água doce; Peixe - distribuição geográfica; Região neotropical; Ecologia; CIENCIAS BIOLOGICAS::ECOLOGIA